DIVERSIFIKASI RASA DAN KEMASAN KRUPUK PULI UNTUK MENINGKATKAN PENJUALAN - Cholilul Chayati; Lutfiana Lutfiana; Endang Widyastuti Sutrisno (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2018)
Puli crackers is one of the traditional crackers in Sumenep, crackers pulleys nowadays have only one variation of flavor that is savory and usually eaten with sambal, which we try to offer different variations that are spicy flavors with different levels of spiciness that consumers more interested and more like the new flavors that spiciness is at levels ranging from 1.2 and 3. try spicy flavor because people do not have to bother anymore to consume these crackers with sambal be more practical and more in line with consumer tastes enthusiasts. Culinary cheese flavor is much preferred by children as well as containing high calcium are suitable for growing children. By flavor of cheese crackers are also more modern pulleys so consumen not only among middle down, but for the middle class and above. The problems of this implementation is the skill in terms of diversification of products still need to be improved, not an increase in sales, product packaging less attractive. While the result of performance of the implementation of these activities have been carried out training skills of making variations of taste and packaging have training for the manufacture of two flavors are spicy taste and flavor of cheese in two Gapoksa who have become partners in this activity. After the training is held in the manufacture of packaging done with automated tools that electrical packaging tool that can achieve results in durable in a long period of time. Innovation in packaging products using plastic packaging stand-up pouch type of PET and PE with a thickness of 0.8 microns is suitable for packaging snack packs with each pack weighs 150 grams and is also equipped with a paper tote bag with attractive colors and innovative. An increase in sales of mature products or packaging that has been fried with a more modern and more innovative flavors.